AB0266 Baseline CD4+ T Lymphocyte Count Predicts Clinical Response to Rituximab in Rheumatoid Arthritis. (10th June 2014) - Stradner, M.H.; Dejaco, C.; Brickmann, K.; Graninger, W.B.; Brezinschek, H.-P.
Abstract : Background: B cell depletion with rituximab (RTX) is an effective treatment strategy for Rheumatoid Arthritis (RA). However, a considerable proportion of patients fail to respond to this treatment, particularly after previous therapy with tumor necrosis factor-α inhibitors. Objectives: Our study was designed to identify lymphocyte subsets in the peripheral blood of RA patients predictive of clinical response to RTX. Methods: 52 RA patients receiving RTX for the first time were included in this prospective observational study. Clinical assessment, complete blood count and flow cytometry of lymphocyte subsets were obtained at baseline as well as at weeks 2 and 24 after RTX. Logistic regression and receiving operating characteristic (ROC) curve analyses were conducted to identify predictors for EULAR response at week 24. Results: Total lymphocyte count (TLC) at baseline was significantly lower in EULAR moderate and good responders compared to non- responders ( P =0.007). We also observed a lower T lymphocyte count in moderate and good responders than in non-responders ( P =0.008). Among the T-cell subsets we found higher levels of CD4 + T cells in non-responders compared to moderate and good responders ( P =0.024). Multivariate logistic regression indicated that TLC was an independent and significant negative predictor of EULAR response (OR 0.853 [0.737-0.987] per TLC increase of 100 lymphocytes/μl, P =0.033). Also, CD4 + T cell count was confirmed as an independent and significant negative predictor of EULAR response (OR 0.805 [0.665-0.975] per CD4 + T cell count increase of 100 cells/μl, P =0.027). A baseline TLC of <1645/μl predicted EULAR response with a high specificity of 91% (sensitivity 40%). A baseline CD4 + T cell count of <1126/μl predicted EULAR response with a specificity of 91% and a sensitivity 66%. Conclusions: Baseline TLC and particularly CD4 + T lymphocyte count reliably predict clinical response to RTX in RA patients. Disclosure of Interest: M. Stradner: None declared, C. Dejaco Paid instructor for: Speakers fees from Hoffmann-La Roche, Austria, K. Brickmann: None declared, W. Graninger: None declared, H.-P. Brezinschek Grant/research support: Unrestricted research grant by Hoffmann-La Roche, Austria DOI: 10.1136/annrheumdis-2014-eular.3554